The political challenges facing the integration of Bulgaria into the European Union - autor, Sin (Papeles del Este, 2004)
The integration of Bulgaria into the European Union is a voluntary process and is the major goal of the foreign policy of the state after the beginning of the changes on 1989. The unification of more than 25 states in the beginning of the 21 century is a tendency without analogue in world political history. The inclusion of Bulgaria in this tendency is a chance for the state, as this will basically provide it with a place among the prevailing trends of world development. Bulgaria needs to participate actively in the debate for the future of Europe. The problem is to find a political formula for integration in the European Union. The current text aimed to outline the fundamental political challenges facing our country in the process of integration. The restructuring of the political space, the change of the functions of the Bulgarian political institutions, as well as social change are the basic lines along which the political elite of the state should work. The European priorities should not determine the foreign relations of Bulgaria, even the opposite; they should be matched with interests in other directions. The integration of Bulgaria into the European Union has to become a factor in the development of relations with other countries. Bulgaria has to walk on its own the path to membership in the European Union, and to make the necessary “sacrifices”.